Falling rock: stories - Varnadore, Heather S. (Kansas State University, 2008)
This project is a novel-in-stories that revolves around the misadventures and exploits of Povi McDougal, head diversity consultant for G & K, responsible for the aggressive sensitivity training of new hires in the company's bid to avoid future lawsuits. She is a nervy, disenfranchised, high-functioning alcoholic. When you think Povi, think binaries: she's a big-hearted misanthrope. She is furious yet wistful, edgy yet vulnerable, knowing yet obtuse, gas yet electric, etc. The stories are all narrated by Povi and are voice, language and character-driven. As a series of connected stories, the action is not in service to one primary plotline. There is, however, a narrative drive that treats Povi's dawning realization of and efforts to come to grips with, her personal and ethnic identity, her abandonment issues and self-imposed isolation. Central to these stories is a synthetic folklore. As a child, Povi's father enrolled her in the Indian Princesses youth group at the YMCA in a misguided attempt to help her connect more fully with her Native American heritage. Figuring prominently in the girls' mythology was the tale of Falling Rock, the highly sought Indian princess who wanders into the woods to escape the fray of young braves who seek her hand in marriage. "Legend" has it Falling Rock becomes lost and is never heard from again. The group's participants are told to be on the lookout for her whenever they see a yellow road sign bearing her name. In short, Povi is my Princess Falling Rock. Given her sense of disinheritance, it seems fitting that her folklore is synthetic, invented. Basically, I've gotten her to wander off into the woods for a bit of solitude, and have kept her there for a while, as she tries to find her way back to her tribe – or some such suitable substitute for tribal affiliation, community, love, what have you.
Keywords: Falling Rock; Fine Arts (0357)